Pengaruh Kepemimpinan dan Pelatihan terhadap Kompetensi Digital yang Dimediasi oleh Motivasi pada Pegawai Kantor Perwakilan Bank Indonesia Provinsi Riau - Irawati, Yunelda; Hendriani, Susi; Setiawan, Deny (Program Studi Manajemen FEBM UMRAH, 2024)
As technological developments accelerate the digitalisation of the financial sector, and to achieve high-performing and productive human resources, Bank Indonesia focuses on improving competencies, especially digital competencies. Currently there are HR training challenges that must be in line with digital megatrends and digital business processes. In addition, there is a need for leaders who are not static, but agile and highly committed to developing organisational transformation values. Bank Indonesia also needs to maintain employee motivation that can support the realisation of competent, professional and high-performing human resources. This study aims to analyse and examine the effect of leadership (X1) and training (X2) on digital competence (Y) mediated by motivation (Z) in employees of the Representative Office of Bank Indonesia Riau Province, with a quantitative approach, using saturated sampling technique to 50 employees and PLS-SEM data analysis tools. The results showed that (1) leadership has a negative and insignificant effect on digital competence, so it must be mediated by other variables to build employee awareness of the value of their work and strive for optimal competence; (2) leadership has a positive and significant effect on motivation; (3) training has a positive and insignificant effect on digital competence; (4) training has a positive and significant effect on motivation; (5) motivation has a positive and significant effect on digital competence; (6) leadership has a positive and significant effect on digital competence through motivation variables; and (7) training has a positive and significant effect on digital competence through motivation variables. Furthermore, it is suggested that it is necessary to strengthen the role of leaders in carrying out all functions in organisational management effectively, as well as increasing the effectiveness of competency assessment in work units.